Severe Hypophosphatemia Occurring After Repeated Exposure to a Parenteral Iron Formulation. (7th October 2022) - Haridas, Keerthana; Yau, Alice
Abstract : Hypophosphatemia is a less known complication of parenteral iron use, particularly after the use of certain iron formulations. We report the case of a young male with inflammatory bowel disease and iron deficiency anemia, who developed severe symptomatic hypophosphatemia after his third exposure to iron carboxymaltose with no evidence of the same occurring upon prior exposures to the compound. Investigations revealed serum phosphorous levels of 0.7 mg/dl, corrected serum calcium of 8–9.5 mg/dl, alkaline phosphatase of 50 U/L (38–126), 25 hydroxy vitamin D level of 40.2 ng/ml, and intact PTH elevated to 207 pg/ml. Urine studies indicated renal phosphate wasting. Presentation was not in keeping with refeeding syndrome. Intact fibroblast growth factor 23 level, measured after the initiation of treatment was within the normal range at 179 RU/mL (44–215). 1, 25 dihydroxy vitamin D level, also measured after the initiation of treatment, was normal at 26.3 pg/ml (19.9–79.3). The patient was treated with calcitriol and aggressive oral and intravenous phosphorous repletion. Symptoms then resolved and the patient was discharged on an oral regimen. This phenomenon is postulated to occur due to an increase in the level and activity of FGF23 and decreased cleavage of the same, due to anemia as well as use of specific iron formulations. This is the first instance, in our literature review, of this complication known to occur, not after initial exposure to an implicated iron formulation but occurring on subsequent exposure.